Muḥammad Sayyid Ṭanṭāwī on Ijtihād: Concept and Typology - Muhammad Lathoif Ghozali (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
This study aimed at exploring the concept and the typology of ijtihād according to Muḥammad Sayyid Ṭanṭāwī. The concept was descriptively expressed while analyzing it using content analysis techniques with a comparative approach. Meanwhile, in scrutinizing the biography and ideas of Ṭanṭāwī, this study utilizes inductive methods and a socio-historical approach to look at his social and political circumstances that the interaction of a mujtahid with his socio-cultural or socio-political environments. The results of the study showed that ijtihād according to Ṭanṭāwī, is an outpouring of the maximum ability of a mujtahid to arrive at the sharī‘ah law by means of istinbāṭ of the sharī‘ah propositions. The area of ​​ijtihād according to Ṭanṭāwī is on the ẓanniyyāt al-thubūt texts such as the Ḥadīth which is a lot of discussion of the Ḥadīth experts about its sanad, validity, weakness and so forth, or ẓanniyyāt al-dilālah, such as the Ḥadīth or the Qur’ān which includes more than one meaning based on the meaning of lughawī or fairness of sharī‘ah. In addition, the Ṭanṭāwī’s typology of ijtihād covers the moderate and middle ground group that pay much attention to maqāṣid sharī‘ah, naṣṣ, and human interests as long as it does not conflict with naṣṣ.